The Effect of Parents' Level of Knowledge About Nutrition on The Nutritional Status of Elementary School Students - Ma'arif, Ilmul (PHEDHERAL, 2023)
The purpose of this study was to determine the effect of parents' knowledge about nutrition on the nutritional status of elementary school students, The method in this study is a type of experimental research using a quantitative approach with pre-experimental design, because in this study there was no control group. The research place at SDN Tenggiring and the research sample with a total of 26 students, the sample sampling technique in this study is purposive sampling technique. The results of this study Based on the table above, it is explained that the calculation of the significance level used α= 0.05, obtained Sig. (2-tailed) is smaller than α (0.033 < 0.05), so it can be stated that there is a significant effect of parental knowledge about nutrition on students' body mass index. Conclusion Based on the purpose of the study and data analysis of the results of research conducted on "the level of parental knowledge of children's nutritional status", it can be concluded that parents' knowledge about nutrition is good, but not maximum awareness about understanding the food consumed. Awareness about the types, products, processes of these foods is still lacking.